Microtensile bond strength between a UDMA fiber post and different resin cements: Effect of pre-surface treatment - Roperto, Renato Cassio; Porto, Thiago Soares; Lang, Lisa; Teich, Sorin; Weber, Sean; El-Mowafy, Omar; Porto-Neto, Sizenando Toledo [UNESP] (Japanese Soc Dental Materials Devices, 2016)
During a fiber post cementation, bonding failure often occurs at the junction between the fiber-post and resin-cement. Because this failure requires better characterization, we evaluated if different post surface treatment can affect the bond strength of urethane dimethacrylate (UDMA) fiber-posts with resin-cements. Three groups were created: Gl: no treatment/silane; G2: ethyl alcohol (96(o) GL)/silane; G3: 24% H2O2/silane and further divided into four subgroups: I-Unicem/3MESPE; II-BisCem/Bisco; III-Panavia SA/Kuraray and IV-DuoLink/Bisco. Blocks of cured resin cements and posts placed in the center were serially cut into bar-shaped specimens and loaded into a micro tensile testing machine. ANOVA indicated no significant differences among post surface treatments (p>0.05), however, significant within the resin cements (p<0.05) and the interaction of both (p<0.05). The G3/IV showed the highest bond strength values. SEM showed that surface treatments on UDMA fiber posts presented no benefits in terms of surface roughness, thus, should not be performed.
Keywords: Adhesion; Fiber-posts; Resin-cements